Dakwah pada Masyarakat Marginal Perkotaan (Studi Kasus Kota Padang) - Mahmuda, Mardan; Bukhari, Bukhari (Jurnal at-Taghyir, 2020)
Abstract: Da'wah activities should be able to attract attention and be able to be a surefire alternative for marginalized communities to solve their life problems, especially problematics on economic aspects. In other words, "da'wah and marginal society" should not be separated for the empowered Islamic community from all aspects. Da'wah is a glorious task for the da'i to make mankind achieve the happiness of the world and the hereafter including the marginal community. This article is compiled using qualitative methods through a literature study approach and field study. Literary studies were conducted based on studies of several literature, such as books and scientific journals relating to da'wah and marginal societies. Later, field studies were conducted by collecting field data through observation techniques and live interviews. In this article about da'wah and marginal community theoretically, loading field data related to da'wah phenomenon and marginally community including explaining about da'wah approach towards marginally. This study is expected to be a contribution to the scientists and practitioners of da'wah, empowerment agencies, religious institutions and other social institutions to empower the marginal community to a maximum and continuously. Â Keywords: Da'wah, Community, MarginalÂ  Abstrak: Kegiatan dakwah seharusnya mampu menarik perhatian dan mampu menjadi alternatif jitu bagi masyarakat marginal dalam menyelesaikan problematika kehidupan mereka, terutama problematika pada aspek ekonomi. Dengan kata lain, â€œdakwah dan masyarakat marginalâ€ tidak boleh dipisahkan demi terwujudnya masyarakat Islam yang berdaya dari segala aspek. Sebab, dakwah adalah tugas mulia bagi para daâ€™i untuk menjadikan manusia mencapai kebahagiaan dunia dan akhirat termasuk masyarakat marginal. Artikel ini disusun dengan menggunakan metode kualitatif melalui pendekatan studi literatur dan studi lapangan. Studi literatur dilakukan berdasarkan kajian dari beberapa literatur seperti buku dan jurnal ilmiah yang berkaitan dengan dakwah dan masyarakat marginal. Kemudian, studi lapangan dilakukan dengan mengumpulkan data lapangan melalui teknik observasi dan wawancara langsung. Dalam artikel ini memuat tentang dakwah dan masyarakat marginal secara teoritis, memuat data lapangan terkait fenomena dakwah dan masyarakat marginal termasuk menjelaskan tentang pendekatan dakwah terhadap masyarakat marginal. Kajian ini diharapkan dapat menjadi kontribusi bagi para ilmuwan dan praktisi dakwah, agen pemberdayaan, lembaga-lembaga keagamaan dan lembaga-lembaga sosial lainnya untuk memberdayakan masyarakat marginal secara maksimal dan berkesinambungan. Â Kata Kunci: Dakwah, Komunitas, Marginal